Cancer cure for 32 cancer types: results from the EUROCARE-5 study. (28th September 2020) - Dal Maso, Luigino; Panato, Chiara; Tavilla, Andrea; Guzzinati, Stefano; Serraino, Diego; Mallone, Sandra; Botta, Laura; Boussari, Olayidé; Capocaccia, Riccardo; Colonna, Marc; Crocetti, Emanuele; Dumas, Agnes; et al.
Abstract: Background: Few studies have estimated the probability of being cured for cancer patients. This study aims to estimate population-based indicators of cancer cure in Europe by type, sex, age and period. Methods: 7.2 million cancer patients (42 population-based cancer registries in 17 European countries) diagnosed at ages 15–74 years in 1990–2007 with follow-up to 2008 were selected from the EUROCARE-5 dataset. Mixture-cure models were used to estimate: (i) life expectancy of fatal cases (LEF); (ii) cure fraction (CF) as proportion of patients with same death rates as the general population; (iii) time to cure (TTC) as time to reach 5-year conditional relative survival (CRS) >95%. Results: LEF ranged from 10 years for chronic lymphocytic leukaemia patients to <6 months for those with liver, pancreas, brain, gallbladder and lung cancers. It was 7.7 years for patients with prostate cancer at age 65–74 years and >5 years for women with breast cancer. The CF was 94% for testis, 87% for thyroid cancer in women and 70% in men, 86% for skin melanoma in women and 76% in men, 66% for breast, 63% for prostate and <10% for liver, lung and pancreatic cancers. TTC was <5 years for testis and thyroid cancer patients diagnosed below age 55 years, and <10 years for stomach, colorectal, corpus uteri and melanoma patients of all ages. For breast and prostate cancers, a small excess (CRS < 95%) remained for at least 15 years. Conclusions: Estimates from this analysis should help to reduce unneeded medicalization and costs. They represent an opportunity to improve patients' quality of life.